COVID-19, Suffering and Palliative Care: A Review - Tan, Seng Beng; Lai, Carol Cheng Kim; Ng, Diana Leh-Ching; Chai, Chee Shee; Tan, Jiunn Liang; Mehul Kumar, Narendra Kumar; Ng, Chong Guan; Lim, Poh Khuen; Lam, Chee Loong; Loh, Ee Chin; Sheriza Izwa, Zainuddin; David Paul, Capelle; et al. (SAGE, 2021)
According to the WHO guideline, palliative care is an integral component of COVID-19 management. The relief of physical symptoms and the provision of psychosocial support should be practiced by all healthcare workers caring for COVID-19 patients. In this review, we aim to provide a simple outline on COVID-19, suffering in COVID-19, and the role of palliative care in COVID-19. We also introduce 3 principles of palliative care that can serve as a guide for all healthcare workers caring for COVID-19 patients, which are (1) good symptom control, (2) open and sensitive communication, and (3) caring for the whole team. The pandemic has brought immense suffering, fear and death to people everywhere. The knowledge, skills and experiences from palliative care could be used to relieve the suffering of COVID-19 patients.